Impact Of Red Velvet Mite, Trombidium Grandissimum Koch In Immune And Microbial System Of Swiss Albino Mice - LIGHTY GEORGE (International Journal of Pharma and Bio Sciences, 2011)
Attempts were made to study the effect of haemolymph of Trombidium grandissimum on gut bacterial population in rodents and its impact on immune system. Total heterotrophic bacterial population densities in gut increased considerably, it will lead’s to enhance immune system. Increment in B-Lymphocyte was much pronounced in test samples exposed mice in the first week and second week also had more or less similar impact on B-cell estimations. The present study, clearly confirm the increment in B-cell number in mouse exposed to test samples. The increase in total heterotrophic bacterial population (THBP) in different regions of the gut due to samples treatment indicated the increase in beneficial probiotic microbes. The increment of beneficial gut micro flora had interfered with the digestive ability, food consumption energetic and overall health of the animal. Feeding and changes in the energy budget also questions the functioning of immune system and execution of immune response. Changes in the energy budget were one of the reasons for modulation to the immunological parameters and immunity. The immunostimulant potential in the haemolymph of Red velvet mite suggests that the mite possess bioactive compounds and this has to be explored in future.